O właściwościach przestrzeni zjawisk regionalnych - Ponikowski, Henryk (Attributes of Regional Factor Space, 2006)
A region can be defined and formalized by describing a set of places and their factors. One can emphasize that the terms: place and fundamental set primary which are terms do not have to be defined. The set of places creates space which keeps the spatial continuity in direct relations in the neighborhood. In practice, this set of places (space) is entitled as region in an administrative way. The set of factors characteristic for analyzed places composes regional factor space. There is some kind of space, characterized by its specific attributes. These attributes arise from relations between factors, emerging places and time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 193-203